The Rebellion Indication Towards Sovereign Government In Acts of Terrorism in Indonesia In Transcendental Dimension - Irfan Hielmy; Nur Rohim Yunus (Fakultas Syariah dan Hukum, UIN Syarif Hidayatullah Jakarta, 2018)
Abstract:Every individual is certainly needing a peace and safety on their life. A terror or an intimidation need to be avoided, and becomes a government’s obligation to protect them. Terror is still occurred in various parts of the world including Indonesia, and a kind of organized crime. This crime is usually called by terrorism. A view which committing acts of violence and threat to create an atmosphere of terror or fear to the people extensively and cause victims spreadly, by snatching independence or loosing life and property, and causing a damage and destruction of life and property of another person. This crime also causes a disruption of national stability. So, the government has an obligation to eradicate and eliminate this criminal group. Unfortunately, terrorism is identifically referred to a specific Islamic group. Whereas Islam is never taught any violence through this humanity, but a religion which taught to keep and protect life. This paper is aim to analyze is terrorism belonging to rebellion as a kind of criminal, or a basic criminal. By using statute approach and transendental approach, the writer makes serious effort to find a conclusion of this problem.Keywords: Rebellion, Terrorism, Sovereign GovernmentAbstrak: Setiap orang pasti menginginkan kedamaian dan keamanan dalam hidupnya. Teror ataupun intimidasi merupakan hal yang harus dihindari, dan menjadi kewajiban negara untuk melindunginya. Terjadinya tindakan kejahatan teror masih terjadi di berbagai belahan dunia termasuk Indonesia, dan merupakan bentuk kejahatan terorganisir. Kejahatan ini biasa disebut dengan terorisme. Sebuah paham yang melakukan tindakan kekerasan dan ancaman guna menimbulkan suasana teror atau rasa takut terhadap orang secara meluas dan menimbulkan korban yang bersifat masal, dilakukan dengan cara merampas kemerdekaan atau hilangnya nyawa dan harta benda orang lain, serta mengakibatkan kerusakan dan kehancuran terhadap nyawa dan harta benda orang lain. Kejahatan ini mengakibatkan gangguan stabilitas nasional. Sehingga pemerintah yang berdaulat berkewajiban membasmi dan menumpas tuntas kelompok pelaku kejahatan ini. Mirisnya, kejahatan terorisme ini kerap diindentikkan kepada kelompok Islam tertentu. Padahal Islam tidak mengajarkan kejahatan terhadap kemanusiaan ini, tetapi agama yang menjaga dan melindungi kehidupan. Penelitian ini mencoba menganalisis apakah terorisme termasuk ke dalam perbuatan kejahatan pemberontakan atau hanya kriminal biasa. Dengan melakukan pendekatan hukum (statute approach) dan pendekatan transendental akhirnya penulis berupaya mencari titik akhir sebagai hasil kesimpulan dari permasalahan ini. Kata Kunci: Pemberontakan, Terorisme, Pemerintahan Berdaulat